Contribution of professional basketball players according to the specific position and the competition phase - José A. Fernández-Cortés; Manuel Gustavo Mandly; Javier García-Rubio; Sergio Jose Ibáñez (Federación Extremeña de Balonmano; University of Extremadura, 2021)
The intervention of female basketball Players during competition has not been widely studied. In addition, it is necessary to differentiate their intervention according to the specific position they occupy. The intervention of the Players is in turn conditioned by the competitive phase. The objectives of this work were to identify the differences in the performance indicators in professional basketball Players based on their role and discover the differences in the performance indicators based on the competition phase. For this, an empirical, descriptive and observational study was carried out, analyzing 572 matches of the 78 days of the regular phase and 20 of the Play-Offs between the 2015/2016, 2016/2017 and 2017/2018 seasons. The game indicators recorded by the competition were normalized according to the minutes Played in order to make comparisons. The Mann-Whitney U Test was performed to identify differences in performance indicators between specific roles in function of competition phase. A change in the intervention of the Players is identified depending on the competition phase. The bases have a greater contribution in the field shots and 2 points during the regular league. Guards and power forwards increase their effectiveness in the Play-Offs on 3-point shooting. Power forwards during the regular season provide more free throws. Finally, during the PlayOffs, the collective game is favored by the contribution of the bases through assists and the defensive game with the contribution of the pivots, through rebounds and the defensive intensity of the forwards. Relevant information can have important applications such as training preparation, prior planning of the competition, making changes to matches, specific instructions on Players and making signings that meet the needs of the team.